INTEGRATION OF ISLAM AND BHOKA CULTURE IN THE WEDDING PROCESSION OF MUNA ETHNICITY IN SOUTHEAST SULAWESI - Astum, Habi (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2024)
ABSTRACTMarriage in Muna society is generally conducted based on customs and religious teachings. The practice of bhoka in the traditional marriages of the Muna tribe was first established by King Sugi Manuru in the 16th century, before the advent of Islam in Muna. The uniqueness of the bhoka tradition lies in the requirement that Muna traditional weddings must involve a specific bhoka determined by social class. This study explores the concept of bhoka for the Muna ethnic group, the integration of Islam and the bhoka culture explained through the functions of bhoka that align with Islamic principles, the influence of social stratification on bhoka determination, and the impact of implementing bhoka in Muna ethnic marriages. The research method employed in this study is the historical, using heuristics, verification, interpretation, and historiography. The results of the study indicate that the integration of Islam and the bhoka culture is evident in the function of bhoka as a marriage dowry, in line with Islamic teachings that require a dowry as a valid condition for marriage in Islam. Keywords: Functions; Social Stratification; Traditional Marriage ABSTRAKPernikahan dalam masyarakat Muna pada umumnya dilakukan berdasarkan adat dan ajaran agama yang dianut. Pemberlakuan bhoka dalam pernikahan adat suku Muna pertama kali diciptakan oleh Raja Sugi Manuru pada abad ke 16 M, yakni di masa sebelum masuknya Islam di Muna. Keunikan dari adat bhoka yaitu pelaksanaan pernikahan etnis muna harus menggunakan bhoka yang ditentukan berdasarkan golongan masyarakat. Penelitian ini membahas konsep bhoka bagi etnis Muna, Integrasi Islam dan budaya bhoka yang dijabarkan melalui fungsi bhoka yang selaras dengan prinsip-prinsip Islam, pengaruh stratifikasi sosial terhadap penentuan bhoka dan dampak pemberlakuan bhoka di pernikahan etnis Muna. Metode yang digunakan dalam penelitian ini adalah metode sejarah yaitu heuristik, verifikasi, interpretasi dan historiografi. Hasil penelitian menunjukkan bahwa integrasi Islam dan budaya bhoka terletak pada fungsi bhoka sebagai mahar pernikahan yang sejalan dengan ajaran agama Islam yang mewajibkan mahar sebagai syarat sah nya pernikahan dalam Islam. Kata Kunci:; Fungsi; Pernikahan Adat, Stratifikasi Sosial.